Bolivia - Brasil - Cuba - Panamá - Chile - EE. UU - ECA: Estudios Centroamericanos (ECA: Estudios Centroamericanos, 1968)
No hay resúmenes disponibles. ECA Estudios Centroamericanos, Vol. 23, No. 239, 1968: 183-189.